MicroRNA-1 effectively induces differentiation of myocardial cells from mouse bone marrow mesenchymal stem cells. (2nd October 2016) - Zhao, Xiao-Ling; Yang, Bo; Ma, Li-Na; Dong, Yan-Hua
Abstract: In this research, bone marrow mesenchymal stem cells (BMSCs) were isolated from mouse, and induced differentiation into myocardial cells in vitro after overexpression of miR-1a. The results showed that the BMSCs could induce differentiation into myocardial cells under the special condition medium, but when the miR-1a was over-expressed in BMSCs, the differentiation efficiency and induction time of myocardial cells from BMSCs could be promoted. This reason was demonstrated that Delta-like 1 (Dll-1) was a transcriptional repressor of myocardium gene expression during myocardium differentiation, miR-1a reduced Dll-1 levels, leading to the accumulation of myocardium gene mRNA and a dramatic increase in myocardium gene protein.